2019
DOI: 10.1186/s12883-019-1541-x
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors to quality of life after vertebral artery dissection: a prospective comparative study

Abstract: BackgroundVertebral artery dissection (VAD) may cause cerebral ischemia and impair quality of life (QOL) despite of good functional outcome. The aim of this study was the multimodal analysis of patient characteristics after VAD to identify contributing factors.MethodsIn an exploratory study, 34 consecutive patients with first-ever spontaneous VAD were prospectively examined in comparison to 38 patients with cerebral ischemia without dissection and 25 stroke mimics as control groups. Multimodal assessment was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…In the present study, mRS score also indicated a significant differences association with QOL. These findings were consistent with Strege and et al [23] who found that functional disability reported by mRS score at follow-up was significantly associated with a reduced model of both univariate and multivariate regression analysis model of QOL. In a cross-sectional study by Ali and et al [24], mRS score captured more quality of life information than either NIHSS or BI scores.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, mRS score also indicated a significant differences association with QOL. These findings were consistent with Strege and et al [23] who found that functional disability reported by mRS score at follow-up was significantly associated with a reduced model of both univariate and multivariate regression analysis model of QOL. In a cross-sectional study by Ali and et al [24], mRS score captured more quality of life information than either NIHSS or BI scores.…”
Section: Discussionsupporting
confidence: 92%
“…21 Two more studies were from the CADISP group and had two different first authors, from which the most recent study was selected which also had the biggest number of patients in the sCeAD arm. That resulted in 17 studies 8,16,17,20,21,[24][25][26][27][28][29][30][31][32][33][34][35] to be included in the qualitative and quantitative synthesis (including studies cited in tables 1 and 2). Figure 1 shows PRISMA study flow diagram.…”
Section: Study Selectionmentioning
confidence: 99%
“…This athlete continued to suffer from ongoing symptoms post-discharge and subsequently died in the intensive care unit (ICU) following a return trip to the ER [ 28 ]. The failure to adequately detect and manage vertebral artery dissection clearly can lead to neurologic sequelae and/ or death [ 85 , 86 ]. Yet, the variety of clinical presentations make it difficult for physicians to make a correct diagnosis, particularly when confronted by an unconscious athlete, on or off the field of play with the potential of spinal injury, or in the ER with limited symptomatology.…”
Section: Discussionmentioning
confidence: 99%